Elevated Plasma Fibrinogen Is Associated With Excessive Inflammation and Disease Severity in COVID-19 Patients - Sui, Jingrui; Noubouossie, Denis F.; Gandotra, Sheetal; Cao, Liyun (Frontiers in Cellular and Infection Microbiology, 2021)
Background The coronavirus disease-19 (COVID-19) is characterized with intense inflammatory response, cardiac involvement, and coagulopathy. Fibrinogen, as a biomarker for inflammation, cardiovascular disease, and coagulation, has not been fully investigated yet. The aim of this study was to assess the clinical application of fibrinogen in COVID-19 patients. Methods We retrospectively analyzed the demographic and laboratory characteristics of 119 COVID-19 patients in the University of Alabama of Birmingham Medical Center. Correlations of fibrinogen on admission with intensive care unit (ICU) admission, disease severity, and laboratory parameters were analyzed. Results Among the 119 COVID-19 patients, 77.3% (92/119) had severe disease, and 59.5% (71/119) patients were admitted to the ICU. Elevated fibrinogen was detected in 67.2% (80/119) of the patients. Fibrinogen levels were significantly associated with inflammatory markers and disease severity, but not with cardiac injury biomarker high sensitivity troponin I. Patients with severe disease had increased fibrinogen levels upon admission compared to patients with non-severe disease (P = 0.001). Fibrinogen level at 528.0 mg/dl was the optimal cutoff to predict disease severity, with a sensitivity and specificity of 66.7% and 70.3% (area undty -60er the curve [AUC] 0.72, P = 0.0006). Conclusions Fibrinogen is commonly elevated in COVID-19 patients, especially in those with severe disease. Elevated fibrinogen correlates with excessive inflammation, disease severity, and ICU admission in COVID-19 patients.